(3GdJYbHGJ Ydi GdehVhYGJs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s ((3Ydi Hf eMeO GdeOfi s)
(3ChdgG (B:s
(3GdMeO ddg (B,(3HYO , aEf cJGH (B" (3GdehVhYGJ (B" (3LeY GdEeGe Hf GdLhRi bO fHg GdMaGX bOjekG hMOjKkG Ydi Cf ajg JSGgdkG cKjQkG hCMGOjK djSJ ehVhYI s
(3BNQgG (B:s
(3hdjS ai ESfGOgG eJge HGdcPH gcPG BNQ eG ChQOJe ai gPG GdcJGH hgPG BNQg hddg GdMeO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG ebGHdI ef fGSNgG SfI (B1102(3g`s
(3Ydi ghGeTgG JUMjMGJ s
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs